1995
DOI: 10.1161/01.str.26.6.976
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Training With Partial Body Weight Support Compared With Physiotherapy in Nonambulatory Hemiparetic Patients

Abstract: Treadmill training offers the advantages of task-oriented training with numerous repetitions of a supervised gait pattern. It proved powerful in gait restoration of nonambulatory patients with chronic hemiparesis. Treadmill training could therefore become an adjunctive tool to regain walking ability in a shorter period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
269
2
22

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 543 publications
(299 citation statements)
references
References 15 publications
6
269
2
22
Order By: Relevance
“…Previous studies showed in accordance with these ideas that the brain networks subserving passive movement and overt execution overlap strongly (Carel et al, 2000;Puce et al, 1995;Weiller et al, 1996;Yetkin et al, 1995) (but see Mima et al, 1999). Again, evidence suggests that passive movement can be successfully applied in motor rehabilitation (Dechaumont-Palacin et al, 2008;Hesse et al, 1995;Lewis and Byblow, 2004;Lindberg et al, 2004;Ward et al, 2006) (but see Lotze et al, 2003). Because the overt movement of the limb in passive movement is not controlled by the participant, we consider the passive movement condition used in the present manuscript as a covert movement mode as well.…”
Section: Introductionmentioning
confidence: 60%
“…Previous studies showed in accordance with these ideas that the brain networks subserving passive movement and overt execution overlap strongly (Carel et al, 2000;Puce et al, 1995;Weiller et al, 1996;Yetkin et al, 1995) (but see Mima et al, 1999). Again, evidence suggests that passive movement can be successfully applied in motor rehabilitation (Dechaumont-Palacin et al, 2008;Hesse et al, 1995;Lewis and Byblow, 2004;Lindberg et al, 2004;Ward et al, 2006) (but see Lotze et al, 2003). Because the overt movement of the limb in passive movement is not controlled by the participant, we consider the passive movement condition used in the present manuscript as a covert movement mode as well.…”
Section: Introductionmentioning
confidence: 60%
“…Nevertheless, recent research studies have shown that aggressive rehabilitation beyond this time period, including treadmill exercise with or without body weight support, increases aerobic capacity and sensorimotor function. 14,16,17,44 Consequently, rehabilitation programs designed to optimize functional motor performance in stroke survivors increasingly have incorporated aerobic exercise training, with and without partial body weight-supported walking, to improve strength and timing of muscle activations and cardiorespiratory fitness. 11,14 -17,20,21,44,45 Generally, this is complemented by specialized training to improve skill and efficiency in self-care, occupational, and leisure-time activities.…”
Section: Goals Of Prescribed Physical Activity/exercisementioning
confidence: 99%
“…11 In the context of defining therapy goals for the poststroke patient, it is essential that the family be integrated into the process as early as possible. Early involvement of the family unit has been strongly correlated with patient adherence to therapy, better understanding between patient and caregiver of achievable outcomes, and improved communication between patient and • 40%-70% peak oxygen uptake; 40%-70% heart rate reserve; 50%-80% maximal heart rate; RPE 11-14 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) caregivers. 79 To facilitate optimal outcomes from an exercisebased stroke rehabilitation program, an assessment of familial support should be undertaken.…”
Section: Barriers To Physical Activity and Exercise Training In Strokmentioning
confidence: 99%
“…1 Task-oriented locomotor training is stated to be an essential factor in the recovery of locomotion. [2][3][4] To achieve locomotion, one must coordinate several motor and cognitive functions, eg, to maintain balance (postural control), to transfer and support the body mass on one limb during stance phase, to clear the floor during the swing phase of the feet, and to apply propulsive force for forward progression. Cognitive prerequisites include motivation and the ability to apply control strategies and to learn and recall motor patterns.…”
mentioning
confidence: 99%